ESG Performance, Busy Directors, Dividend Payout Policy And Moderating Role Of Ownership Concentration: Indonesian Evidence - Ni Putu Diah Sucitawati; Cynthia Afriani Utama (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study examines the relationship between ESG performance, busy directors, and corporate dividend policies, moderated by cash flow rights and control rights. Using panel data regression analysis, the research focuses on non-financial firms listed on the Indonesia Stock Exchange from 2017 to 2022. As Indonesia's capital market grows, companies face pressure to create stakeholder value while remaining competitive. Investors push firms to balance ESG investments with shareholder rewards. The presence of busy directors, serving on multiple boards, raises questions about their impact on dividend policies. Given Indonesia's concentrated market, this study introduces ownership concentration as a moderating factor, addressing a gap in the literature. The results show that ESG performance and busy directors positively impact dividend policies. Firms with strong ESG practices maintain consistent dividend payments, reflecting their commitment to stakeholders and shareholders. Busy directors improve dividend policies, aligning with the perception of high-caliber boards reducing agency costs. Cash flow rights moderate the impact of ESG performance on dividend policies, while control rights weaken this influence. However, neither variable significantly affects the relationship between busy directors and dividend policies. This research provides insights into the interplay between ESG practices, director commitments, and dividend policies in Indonesia's dynamic business environment.